Pemberian Pakan dengan Energi yang Berbeda Terhadap Pertumbuhan Benih Ikan Kerapu Tikus (Cromileptes altivelis) [Feeding with Different Energy To Growth Of Groupers (Cromileptes altivelis) ] - Agustono, Agustono; Widiana Permata sar; Yudi Cahyoko (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractGrouper (Cromileptes altivelis) is a kind of coral reef fish that only lives and grows fast in tropical areas. The grouper fish (Cromileptes altivelis) is one of high economy value sea fishes. One of the ways to increase the grouper fish (Cromileptes altivelis) production is by enhancing the feeding management. The energy feeds are the ones containing high energy. High energy is able to improve the feeding efficiency and the increasing weight of grouper fish (Cromileptes altivelis) and to reduce the water contamination. The research is aimed to know the influence of the different feeding energy to the growth rate, feed efficiency, fat content and the survival rate of grouper fry (Cromileptes altivelis). The research method used in this one was the experiment and the applied design was Complete Random Design (CRD) with 5 treatments. The treatments were A (3.263,92 kkal/kg) as controller, B (3.291,59 kkal/kg), C (3.330,62 kkal/kg), D (3.453,35 kkal/kg), E (3.535,35 kkal/kg) and every treatment was repeated four times. The obtained data were analysed by using Analysis of Variance (ANOVA), if there were differences, it will be continued with the Duncan Multiple Range Test (DMRT). The research showed that the daily growth rate, the feed efficiency, the fat content and survival rate of grouper fry were the same respectively (p>0.05).